Sharpening our tools : improving evaluation in adult and nonformal education - Easton, Peter A. (Unesco Institute of Education HamburgDE, 1996)
Addresses some of the conceptual and theoretical issues underlying evaluation practice and deals with technical aspects of evaluation design. Focuses on several particular methodologies of evaluation that could stand to receive greater emphasis in non formal education (NFE). Offers some brief conclusions regarding the professional development of NFE evaluators and its relation to broader popular participation in educational planning and evaluation.